ENGLISH AS AN INTERNATIONAL LANGUAGE AND ITS VARIETIES - Rahmonova, Gulhayo Khalilovna (INTERNATIONAL CONFERENCES, 2023)
In the last decades, the term “English as a Lingua Franca” (ELF) has emerged as a way of referring to communication in English between speakers with different native languages. ELF is considered as a contact language between speakers who share neither a native tongue nor a national culture, and for whom English is the chosen foreign language of communication. (Firth 1996). Consequently, a lingua franca is a third language that is distinct from the native language of both parties involved in the communication and sometimes as the language becomes more widespread, the native populations of an area will speak the lingua franca to each other as well. The article analyzes the linguistic processes which are termed contact or interference varieties. The contexts in these varieties are formed blending two or more language’s features. Interference varieties were mostly appeared in Africa and Asia and brought to English the contexts colored with multilingual and multicultural features. These varieties have special characteristics in linguistic levels such as pronunciation, grammar, lexis and discourse. The results showed that the use of certain features in ELF which is regarded as “errors” in Standard English are not considered as problematic and do not disturb communicative success.